2022
DOI: 10.3390/ma15196829
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Reagents on the Synthesis Process and Shape of Silver Nanoparticles

Abstract: The aim of this study was to prepare the silver nanoparticles (AgNPs) via chemical reduction and analyze the impact of used reduction agents: sodium borohydride (NaBH4), trisodium citrate (TSC), polyvinylpyrrolidone (PVP), and hydrogen peroxide (H2O2) on the reduction rate of Ag+ ions to Ag0, and on nanoparticles shape. It was proven that combinations of reduction agents dramatically influence the synthesis rate of AgNPs and the color of solutions, which depends on the shape and size of nanoparticles. NaBH4, T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 37 publications
2
3
0
Order By: Relevance
“…UV–visible spectroscopy to characterize Ag@BO nanoparticles showed an absorption peak at 398 nm (Figure E), consistent with literature reports, proving that Ag@BO nanoparticles were appropriately prepared. Ag@BO nanoparticles, Ag@BON nanoparticles, and E.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…UV–visible spectroscopy to characterize Ag@BO nanoparticles showed an absorption peak at 398 nm (Figure E), consistent with literature reports, proving that Ag@BO nanoparticles were appropriately prepared. Ag@BO nanoparticles, Ag@BON nanoparticles, and E.…”
Section: Resultssupporting
confidence: 90%
“…36−38 With the integration of machine learning technology, the obtained SERS fingerprints were quickly discriminated against and distinguished by the artificial intelligence recognition system (Figure 1D), making the output of SERS fingerprints more intuitive and the interpretation of detection results easier, which contributed to the development of SERS technology in clinical work. UV−visible spectroscopy to characterize Ag@BO nanoparticles showed an absorption peak at 398 nm (Figure 1E), consistent with literature reports, 39 proving that Ag@BO nanoparticles were appropriately prepared. Ag@BO nanoparticles, Ag@BON nanoparticles, and E. faecalis with Ag@ BON nanoparticles were characterized by TEM, and it was found that Ag@BO nanoparticles had a small diameter and a loose distribution (Figure 1F).…”
Section: Resultssupporting
confidence: 89%
“…Reference The preparation method of bare AgNPs and make appropriate modifications ( Bharti et al, 2021 ; Fu et al, 2021 ; Jassim et al, 2022 ; Velgosova et al, 2022 ). 9.45 mg of NaBH 4 Was weighed and added To 25 mL of NaOH solution (0.…”
Section: Methodsmentioning
confidence: 99%
“… The order of reagents was ranked third. The order can affect the nucleation and growth processes involved in synthesis [75] . Controlling the sequence of reagent addition, can influence the formation, capturing critical information about the kinetics and thermodynamics of nucleation and growth, and making it a significant predictor.…”
Section: Resultsmentioning
confidence: 99%